2019
DOI: 10.1097/md.0000000000016395
|View full text |Cite
|
Sign up to set email alerts
|

Scalp melanoma with rectus abdominis metastasis

Abstract: Rationale: The main cause of death in melanoma patients is widespread metastases as it can metastasize to almost every organ. However, melanoma skeletal muscle metastases (MSMM) are exceptional, and only a few cases of MSMM to the rectus abdominis muscles have been previously described. And our case maybe the first reported case in Asia region. Patient concerns: A 45-year-old man with history of right scalp melanoma, pT3aN0M0, stage IIA status post wide excision with 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Dalle Carbonare et al 11 described a patient with melanoma of unknown primary, whose presenting complaint was a temporalis muscle lesion, which appeared as a lobulated high signal mass on T 1 -weighted imaging with no evidence of intralesional fat, with diffusely low signal on T 2 -weighted imaging. A further example a T 1 -hyperintense lesion was described by Pirlamarla et al 12 who reported a case of an elderly female with recurrent vulvar melanoma with extraocular muscle metastasis, appearing as a heterogenous hyperintensity on T 1 -weighted images of orbital MRI, with high signal on T 2 -weighted sequences.…”
Section: Discussionmentioning
confidence: 86%
“…Dalle Carbonare et al 11 described a patient with melanoma of unknown primary, whose presenting complaint was a temporalis muscle lesion, which appeared as a lobulated high signal mass on T 1 -weighted imaging with no evidence of intralesional fat, with diffusely low signal on T 2 -weighted imaging. A further example a T 1 -hyperintense lesion was described by Pirlamarla et al 12 who reported a case of an elderly female with recurrent vulvar melanoma with extraocular muscle metastasis, appearing as a heterogenous hyperintensity on T 1 -weighted images of orbital MRI, with high signal on T 2 -weighted sequences.…”
Section: Discussionmentioning
confidence: 86%